1994
DOI: 10.1002/jor.1100120208
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the normal trapeziometacarpal joint

Abstract: Motion of the trapeziometacarpal joint was studied in 12 hands from fresh human cadavera. By use of a magnetic tracking system, a full range of motion of the first metacarpal was analyzed with respect to a defined trapezial coordinate system. The traces of the reference points on the head and base of the first metacarpal were monitored, and the instantaneous centers of rotation were calculated. During circumduction, the reference points on the head and base followed elliptical paths but in opposite directions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 24 publications
5
36
0
2
Order By: Relevance
“…In a comprehensive marker-based thumb motion study, Tang et al [31] also reported that the first metacarpal generally moves in a direction that is oblique to the anatomy of the CMC joint. In addition, our finding that internal/external rotation of the metacarpal was coupled with flexion/extension and adduction/abduction simultaneously is in agreement with findings from other studies that have reported the flexion/extension and the adduction/ abduction axes as primary axes of motion at the CMC joint and internal/external rotation as a secondary axis of rotation that is coupled with the previous two [8,9,13,15,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a comprehensive marker-based thumb motion study, Tang et al [31] also reported that the first metacarpal generally moves in a direction that is oblique to the anatomy of the CMC joint. In addition, our finding that internal/external rotation of the metacarpal was coupled with flexion/extension and adduction/abduction simultaneously is in agreement with findings from other studies that have reported the flexion/extension and the adduction/ abduction axes as primary axes of motion at the CMC joint and internal/external rotation as a secondary axis of rotation that is coupled with the previous two [8,9,13,15,29].…”
Section: Discussionsupporting
confidence: 92%
“…Yet, a detailed analysis of in vivo 3-D kinematics of the CMC joint has not been reported to date. The existing body of literature is based on cadaver studies [13,15,17,26], skin marker-based studies that track motion of the thumb, but not the trapezium [4,6,9,18,19,21,31], or single-subject imaging studies whose purpose has been to verify that flexion/extension and adduction/abduction are the primary degrees of freedom at the CMC joint [3,7]. Elucidation of OA pathogenesis requires quantitative methods capable of determining both bone rotations (osteokinematics) and articular surface translations (arthrokinematics) and large samples from different demographic groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study advances our understanding of CMC kinematics by demonstrating that coupling of the primary motions with internal-external rotations and translation along the screw axes are continuous functions of the direction of motion. This is in contrast to other studies that have reported minimal or no coupled motions, perhaps because those studies were focused on the primary motions [1,4,[6][7][8]23,[26][27][28], or because the kinematic data were acquired using surface marker-based motion capture systems where skin motion artifact can be large enough to mask the more modest coupled motions. Coupling with internal-external rotations is evident by the nonzero value of ele, in which positive values of ele indicate coupling with internal rotations and negative values of ele indicate coupling with external rotation.…”
Section: Discussionmentioning
confidence: 76%
“…Subsequently, in a review of thumb CMC instability and dislocation, Edmunds proposed that the soft tissues surrounding the CMC joint generate a stabilizing screw-home motion at the end of thumb opposition, indicating a coupling between flexion and internal rotation [2,3]. Previous experimental studies, however, have not reported translational or a rotational coupling motions of the thumb CMC joint consistent with such a screw-home mechanism [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional cadaveric biomechanical studies approximate the force on a joint via applied extrinsic and intrinsic tendon loads and employing mechanical models with simplified joint constructs [26,49,51]. From such models, we understand the progressive force increase from the tip to the CMC joint, with the force across the CMC joint in grasp exceeding that of lateral pinch approximately 10-fold (120 kg versus 12 kg) [25].…”
Section: Next Stepsmentioning
confidence: 99%